PENERAPAN STRATEGI MEMBACA KRITIS DI AKADEMI FARMASI SURABAYA UNTUK MENUNJANG KECAKAPAN LITERASI MENUJU ERA REVOLUSI INDUSTRI 4.0 - Nuria Reny Hariyati; Abdul. Syakur (Universitas Muhammadiyah Semarang, 2018)
The fourth generation industrial revolution is marked by the emergence of advanced technology. Every human activity depends on technology. The challenge of education is to prepare human resources that are invincible with machines. One job that has not been replaced by a machine is the ability to analyze and criticize. The application of critical reading 3 Ter to students needs to be improved to support literacy skills.This research is a quasi experimental study. The data of this study are critical reading scores. Critical reading scores were obtained from tests in grades A1-15 and A2-15 Surabaya Pharmacy Academy.Based on the results of the study, it was concluded that the implementation of the 3 Ter strategy had a significant effect on reading the criteria for classes A1-15 at a significance level of 0.05. The average critical reading score of the class that received 3 Ter treatment was 66.4286, while theaverage critical reading score for the class that did not get 3 Ter treatment was 62.8000. The success is seen in the final test results that have been carried out.. Keywords: Critical Reading, 3 Ter